THE ANALYSIS OF STUDENTS' UNDERSTANDING TOWARD ENGLISH SPEAKING LEARNING MATERIAL DURING THE PANDEMIC ERA IN 8TH GRADE OF JUNIOR HIGH SCHOOL 3 NGADIROJO IN THE ACADEMIC YEAR 2020/2021 - Noni Agus Tina; Dwi Rahayu; Agung Budi Kurniawan (The Journal Of English Teaching For Young And Adult Learners, 2022)
This research aims to know the students' understanding of English-speaking learning material during the pandemic era in the 8th grade of Junior High School 3 Ngadirojo. It is case study research that focused on the students' understanding of speaking learning material. The research used a descriptive qualitative approach. The research subject is students in the 8th grade of SMPN 3 Ngadirojo. The research was conducted from March-May 2021 in an online way. The data collecting techniques used in this research are tests and interviews. The research instruments used to collect the data are material sheets and cell phones. Techniques that are used to analyze data are data reduction, data display, and conclusion. The result showed that most of the students in the 8th grade of Junior High School 3 Ngadirojo can understand the speaking learning material well during online learning in the pandemic era. But not all students could understand the material caused by problems such as internet network connection, learning communication tools, teacher learning techniques, students' ability to understand the material, and other issues. Online learning is one of the most used learning strategies during the pandemic era, even though it could not reach the curriculum target.